Ablation of μ opioid receptor-expressing GABA neurons in rostromedial tegmental nucleus increases ethanol consumption and regulates ethanol-related behaviors. (August 2016) - Fu, Rao; Chen, Xing; Zuo, Wanhong; Li, Jing; Kang, Seungwoo; Zhou, Li-Hua; Siegel, Allan; Bekker, Alex; Ye, Jiang-Hong
Abstract: There has been increasing interest in the rostromedial tegmental nucleus (RMTg), given its potential regulatory role in many aversion-related behaviors. The RMTg contains mostly GABAergic neurons, sends a dense inhibitory projection to dopamine neurons in the midbrain, and is rich with μ-opioid receptors (MOR). Like most addictive drugs, ethanol has both aversive and rewarding properties. However, the cellular mechanisms underlying the effects of ethanol, particularly the aversive effect that limits its intake are not well understood. Recent studies have linked aversion with synaptic inhibition of dopamine neurons in the ventral tegmental area. To determine a potential role that the RMTg plays in the effect of ethanol, in this study, we employed a neurotoxin, dermorphin-saporin (DS), to lesion RMTg neurons prior to assessing ethanol-related behaviors. Rats were infused with DS bilaterally into the RMTg. This manipulation substantially increased the intake and preference for ethanol but not sucrose. It also reduced the number of neurons with MOR and glutamic acid decarboxylase 67 immunoreactivity within the RMTg. These changes did not occur after intra-RMTg infusion of blank saporin or vehicle. Importantly, intra-RMTg DS infusion significantly enhanced expression of conditioned place preference induced by ethanol (2 g/kg, i.p.), and slowed the extinction process. These results suggest that MOR-expressing GABAergic neurons in the RMTg contribute significantly to the regulation of ethanol consumption and related behaviors. Highlights: RMTg infusion of dermorphin-saporin (DS) increased ethanol intake and locomotion. DS infusion reduced protein expression of glutamic acid decarboxylase 67 and MORs. DS infusion decreased neurons with glutamic acid decarboxylase 67 and MOR in RMTg. RMTg DS infusion enhanced ethanol-induced CPP acquisition and slowed CPP extinction.